DOI: 10.35537/10915/55309
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicología y alteraciones morfo-funcionales en gasterópodos marinos expuestos a contaminación por Tributilestaño (TBT) y metales

Abstract: El golfo Nuevo presenta un gradiente de actividad marítima que se refleja en la presencia de contaminantes como Tributilestaño (TBT), metales e hidrocarburos poliaromáticos. Se ha demostrado la relación causa efecto entre la presencia de TBT en el ambiente marino y el desarrollo de caracteres sexuales secundarios masculinos (imposex) en hembras de cenogasterópodos; sin embargo, otros efectos adversos pueden producirse sobre los organismos expuestos a contaminantes durante largos periodos de tiempo. El objetivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 258 publications
(393 reference statements)
0
2
0
Order By: Relevance
“…In the other assessed species, T. geversianus and B. globulosu s, imposex was not detected, probably due to the relatively low level of TBT. In fact, Bigatti et al reported that T. geversianus only presents imposex in high TBT polluted areas, whereas B. globulosus is an indicator of medium TBT pollution . The BTs' discrete pollution was also reflected in S3( s ), (Sara Creek), where small fishing boats operate.…”
Section: Resultsmentioning
confidence: 99%
“…In the other assessed species, T. geversianus and B. globulosu s, imposex was not detected, probably due to the relatively low level of TBT. In fact, Bigatti et al reported that T. geversianus only presents imposex in high TBT polluted areas, whereas B. globulosus is an indicator of medium TBT pollution . The BTs' discrete pollution was also reflected in S3( s ), (Sara Creek), where small fishing boats operate.…”
Section: Resultsmentioning
confidence: 99%
“…In the harbour area of Nuevo Gulf (LPBH), the presence of TBT in sediments (up to 174.81 ng Sn g À1 DW) and in the body of the gastropod O. magellanica (up to 150 ng Sn g À1 DW in gonads) were recently detected in the same sites as we sampled in Nuevo Gulf, Patagonia (Bigatti et al 2009;del Brı ´o 2011). In addition, pollutants such as PAHs (Commendatore and Esteves 2007;Massara Paletto et al 2008;Torres et al 2013) were measured in sediments and, recently, Primost (2014) found heavy metals in the tissue of B. globulosus from the LPBH area.…”
Section: Discussionmentioning
confidence: 99%